2009
DOI: 10.1002/ijc.24264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol analogs on cell cycle progression, cell cycle associated proteins and 5fluoro‐uracil sensitivity in human derived colon cancer cells

Abstract: Epidemiological studies suggested that trans-resveratrol, a wine grape component, could prevent malignant tumor development. This compound also demonstrated cytostatic and cytotoxic effects on tumor cells in vitro. To obtain trans-resveratrol derivatives with a better cellular uptake and enhanced antiproliferative effects, we synthesized a triacetate derivative as well as an oligomer, e-viniferin and its acetylated form, e-viniferin penta-acetate. We also obtained vineatrol, a wine grape shoot extract that ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
95
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 51 publications
10
95
0
1
Order By: Relevance
“…In a similar manner, we have previously shown that lipid rafts play a role in clustering or aggregating surface receptors and adaptor molecules into membrane complexes at specific sites and are shown to be essential for initiating signaling from a number of receptors, particularly in the initiation of Fas-mediated apoptosis during resveratrol treatment (4). These microdomains sequester the polyphenol, as described recently for autocrine motility factor (AMF)/phosphoglucose isomerase (PGI)-paclitaxel (46), and therefore function as a platform that finely tunes up the tumor cell response to this agent, either directly by inducing cell-cycle arrest or cell death (47) or indirectly by sensitizing the cells to chemotherapeutic agents (11,15). This sensitization could involve the inhibition of the H þ -ATP synthase by resveratrol (48).…”
Section: Discussionmentioning
confidence: 97%
“…In a similar manner, we have previously shown that lipid rafts play a role in clustering or aggregating surface receptors and adaptor molecules into membrane complexes at specific sites and are shown to be essential for initiating signaling from a number of receptors, particularly in the initiation of Fas-mediated apoptosis during resveratrol treatment (4). These microdomains sequester the polyphenol, as described recently for autocrine motility factor (AMF)/phosphoglucose isomerase (PGI)-paclitaxel (46), and therefore function as a platform that finely tunes up the tumor cell response to this agent, either directly by inducing cell-cycle arrest or cell death (47) or indirectly by sensitizing the cells to chemotherapeutic agents (11,15). This sensitization could involve the inhibition of the H þ -ATP synthase by resveratrol (48).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, several studies have evaluated novel treatments or 5-FU combination treatments to overcome this drug resistance. Previous studies have demonstrated that co-treatment of cells with genistein and 5-FU reduces the proliferation of colon cancer cells more effectively compared with genistein or 5-FU alone (4), and the co-treatment of colon cancer cells with resveratrol and 5-FU inhibited cell growth more effectively compared with resveratrol or 5-FU alone (25). In the present study, the combination treatment of 5-FU and resveratrol was investigated in order to develop modalities to overcome drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that resveratrol triacetate and vineatrol are efficient in inducing the accumulation of human colon cancer cells in the early S phase of the cell cycle. 24 This effect is associated with a nuclear redistribution of cyclin A and the formation of a cyclin A/cyclin-dependent kinase 2 complex whose kinase activity is increased. 24 Of particular importance, resveratrol triacetate and vineatrol dramatically enhance 5-fluoro-uracil-mediated inhibition of colon cancer cell proliferation.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…24 This effect is associated with a nuclear redistribution of cyclin A and the formation of a cyclin A/cyclin-dependent kinase 2 complex whose kinase activity is increased. 24 Of particular importance, resveratrol triacetate and vineatrol dramatically enhance 5-fluoro-uracil-mediated inhibition of colon cancer cell proliferation. 24 The potential inhibitory effect of the resveratrol derivative on cell proliferation and the…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation